RANCANG BANGUN SISTEM INFORMASI PEMESANAN COFFEE BERBASIS WEB PADA CAFÉ KAHAWA - Rayhan Sulaiman; Nardiono (CV. Multi Kreasi Media, 2024)
Technology is growing rapidly, as well as increasingly visible business competition, companies can take advantage of internet technology that is able to support company activities by building websites in the field of sales to be able to promote their products through websites, websites can be used as a means to transact buying and selling goods or products that make transactions Sales can be made in a relatively short time even though the distance is far apart. Cafe Kahawa is a cafe business that serves coffee sales, not just coffee, there are other menus that are served at Cafe Kahawa. The service has not been maximized in the ordering process, making consumers wait long enough to order. Order data management is not optimal because the ordering process is recapitulated in the books which is seen based on order notes and order reports in daily and one month orders in different books so that the large number of books often results in errors and errors in writing because seeing one note at a time -consumer notes that can take time in making reports. A web-based coffee sales information system with information system development using the waterfall method, and PHP as a programming language, MySql is used to create a database, and tested with black box testing. An information system can be obtained that can speed up the order process at the cafe kahawa and can store order data and order reports quickly and precisely.